A Classroom Approach to Explore Spatial Narratives in Film: The Case of James Bond - Johansson, Ola (Journal of Geography Education, 2025)
This paper examines the ways in which the setting and spatial narratives of films can be mapped and measured by students. In a course dedicated to James Bond, students watched all the films in the series, analyzed how geographically widespread they are, and how patterns unfold and change. James Bond's geography tends to be more dispersed over time, as he travels to more places later in the franchise, which mirrors evolving global geopolitics. The research proved to be effective in conveying spatial concepts and making basic statistical analysis relatable to students without any background in quantitative methods.
Keywords: James Bond, film geography, spatial analysis, geopolitics, film in education